Euro Area Policies : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on Euro Area Policies reviews the integration of Europe's financial markets and the challenges faced by the new European Union member states with respect to euro adoption. Markets in the Financial Instruments Directive are expected to become applicable in November 2007. The Directive injects new competition among financial intermediaries at all steps of a security's transaction cycle, from the provision of investment advice to the practical execution and settlement of the transaction, and thus holds the promise to accelerate Europe's apparently sluggish financial sector productivity growth.